Increasing the Brand Awareness of Go China Using a Promotional Video - Monica Gozali (Institute of Research and Community Outreach - Petra Christian University, 2018)
Asia Holiday Tour & Travel is a travel agency based in Surabaya on Jalan Indragiri No. 12-18 #9. It focuses more on tour package selling especially throughout Asia. Asia Holiday has a main project called Go China that offers many destinations to China. Go China’s target market is Surabaya people, middle to high class, and 40 years old and older. Asia Holiday’s competitors are ATS Vacations and Golden Rama. The main problem of Asia Holiday is that they only have brochures to promote and market their tour products which not so effective. As a result, the selling of Go China tour packages rarely achieves its maximum number. A promotional video is the best solution for Asia Holiday to increase the brand awareness of Asia Holiday. It is an animation video and as a representative in explaining about Go China to the target market.